PENERAPAN METODE ACTIVITY BASED COSTING DALAM MENENTUKAN HARGA POKOK PRODUKSI PADA UMKM BROWNIES MAWAR DI BEKASI - Dwi Hastuti; Arini Siti Sundari; Husna Azizaturrahmah (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the application of the Activity Based Costing (ABC) method in determining the cost of production at Brownies Mawar, a small and medium-sized enterprise (SME) in Bekasi. This SME is a small business that has been producing various types of brownies for more than 20 years, but still uses a conventional cost accounting system. The ABC method allows for more accurate cost allocation by identifying each activity in the production process and assigning costs based on actual resource consumption (cost drivers). Data collection was conducted through observation, interviews, and documentation. The research results show that the production cost per unit using the ABC method is Rp 3,190 for the Original variant and Rp 3,470 for the Combination variant. With selling prices of Rp 25,000 and Rp 30,000 respectively, the SME achieves a high profit margin and a total monthly gross profit of Rp 42,656,400. These findings indicate that the ABC method is effective in providing accurate cost information, uncovering hidden costs, and supporting more competitive pricing strategies.